Spectres of War in Deimantas Narkevičius’s Legend Coming True and Sergei Loznitsa’s Reflections - Brasiskis Lukas (Acta Universitatis Sapientiae: Film and Media Studies, 2022)
This text discusses Deimantas Narkevičius’s Legend Coming True (Legendos išsipildymas, 1999) and Sergei Loznitsa’s Reflections (Отражения, 2012), two films by contemporary artists and filmmakers that revisit war traumas – the Holocaust in Lithuania and the Siege of Sarajevo in Bosnia – indirectly, without narrative reconstruction of the events or use of the archival images to display their atrocities of these two tragedies. Instead, these two experimental films, I argue via Jacques Derrida, evoke spectres of the war in the contemporary urban setups to activate the half-mourning in the present. Aesthetic strategies used to expose the haunting past are closely scrutinized and compared in order to demonstrate the films’ aesthetic potential of walking the spectator through war traumas without departing the present.